The High School Learners` Instrumental Motivation and Its Correlation to the Their English Achievements - Anggeraini, Yentri; Novarita, Novarita; Nandaini, Salsabila P; Lestari, Neti; Yuslinita, Nopa; Afifah, Nurul (Universitas Muhammadiyah Mataram, 2024)
Several studies have focused on extrinsic and intrinsic motivation and their impact on students’ learning progress. This study aimed to explore instrumental motivation and its relationship with English achievement among high school students. This correlational study was conducted at MA Al-Azhar Centre Baturaja with a total of 100 participants. A 20-item questionnaire containing 6 indicators of instrumental motivation was distributed to collect data. English certificate scores in odd semesters were used to record English achievement. Overall, students at MA Al-Azhar Centre Baturaja showed high motivation and good English achievement. Therefore, the overall results of the study confirmed that high motivation category is associated with good English performance. The analysis showed that there is a correlation between instrumental motivation of students at MA Al-Azhar Centre Baturaja and their English achievement. The analysis revealed a strong correlation (coefficient of 0.634, p< 0.05), supporting the acceptance of the alternative hypothesis and rejection of the null hypothesis.